FORMATION OF FOREIGN LANGUAGE SOCIOCULTURAL COMPETENCE BASED ON READING HUMOROUS TEXTS (Conferencea, 2023)
The article discusses the establishment of the structure and content of sociocultural competence based on the definition of principles for the selection of humorous texts, which is substantiated by the theoretical basis for the formation of foreign language sociocultural competence based on reading humorous texts. Initially, the article observes the theoretical foundations of learning to read foreign language texts. Firstly, reading is considered as an independent type of speech activity, when teaching a foreign language, one of the main places in its importance and accessibility. It is considered that reading is one of the main areas of foreign language speech communication in individual work.